2012
DOI: 10.1080/22201009.2012.10872277
|View full text |Cite
|
Sign up to set email alerts
|

The 2012 SEMDSA Guideline for the Management of type 2 Diabetes

Abstract: Raubenheimer P; Guideline Committee. The 2012 SEMDSA guideline for the management of type 2 diabetes. JEMDSA. 2012;17(1):S1-S94.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 217 publications
1
6
0
Order By: Relevance
“…The mean systolic blood pressure of the study participants was 139.68 (± 21.82) mmHg and mean diastolic blood pressure was 79.91 (± 11.13) mmHg, which concurs with the latest targets of less than 140/80 mmHg in type 2 diabetes mellitus patients set out by the SEMDSA guidelines (Amod et al 2012a). These findings concur with the findings of Amod et al (2012b), who also found blood pressure was relatively well controlled, where participants (n = 701) with type 2 diabetes mellitus had mean systolic blood pressures of 132.9 (± 17.5) mmHg and mean diastolic pressure of 80 (± 10.2) mmHg (Amod et al 2012b).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…The mean systolic blood pressure of the study participants was 139.68 (± 21.82) mmHg and mean diastolic blood pressure was 79.91 (± 11.13) mmHg, which concurs with the latest targets of less than 140/80 mmHg in type 2 diabetes mellitus patients set out by the SEMDSA guidelines (Amod et al 2012a). These findings concur with the findings of Amod et al (2012b), who also found blood pressure was relatively well controlled, where participants (n = 701) with type 2 diabetes mellitus had mean systolic blood pressures of 132.9 (± 17.5) mmHg and mean diastolic pressure of 80 (± 10.2) mmHg (Amod et al 2012b).…”
Section: Resultssupporting
confidence: 85%
“…The baseline HbA1c levels of participants were categorised into age group and risk category to establish the proportion of participants with results within and outside target ranges as per the Western Cape Province guidelines (Western Cape Government Health 2012), which are based on SEMDSA guidelines (Amod et al 2012a). In addition to baseline measurements, this study followed the glycaemic monitoring results and the follow-up prescriptions for each participant over an 18 month period.…”
Section: Data Collection and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…It is essential that efforts are made to diagnose diabetes early to prevent the complications and to begin early management interventions of the disease (Ramachandran, 2014). Early control of glycaemia and dyslipidaemia, together with regular examination for macrovascular and microvascular complications, with appropriate and timely interventions, are the only ways to prevent and reduce morbidity and mortality related to diabetes (Amod, Motala, Levitt et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Drivers with diabetes mellitus, similarly, are regarded as higher-risk drivers, owing mainly to the possibility of hypoglycaemic incidents while driving, [7] but also to other potential complications such as stroke, cataracts, or retinopathy. [8] Hypoglycaemia is of particular concern for drivers, as it can result in clumsiness, confusion, seizures, loss of consciousness, and death.…”
Section: Risks Posed By Diabetic Driversmentioning
confidence: 99%